Proyecto lector mediante el Aprendizaje Basado en Proyectos en los estudiantes de Noveno año de la Unidad Educativa Isabel de Godín - Arroba Riofrio, Jennifer Adriana (2024)
Reading comprehension is a skill that students need to develop during their academic training process, with the objective of designing a reading project through project-based learning for ninth grade students at the Isabel de Godín Educational Unit, a qualitative investigation is developed to which used the information collection tools of bibliographic review, direct observation and semi-structured interviews applied to 6 ninth-year students of Basic General Education of the Isabel de Godín Educational Unit, and 2 teachers in the area of language and literature. where, the main finding is that students positively perceive the design of a reading project where they can get involved and integrate their preferences, however, the teachers do not have previous experience in proposing reading projects, therefore, The need to develop a reading project that improves the reading comprehension of the students is concluded, in this way, a proposal for a reading project is designed with the PBL methodology where the students contributed with their preferences and needs